Pentraxin 3 Is a Predictor for Fibrosis and Arterial Stiffness in Patients with Nonalcoholic Fatty Liver Disease - Kadir Ozturk; Omer Kurt; Tolga Dogan; Alptug Ozen; Hakan Demirci; Fatih Yesildal; Murat Kantarcioglu; Turker Turker; Ahmet Kerem Guler; Yıldırım Karslioglu; Battal Altun; Ahmet Uygun; et al. (Gastroenterology Research and Practice)
Objective. The aim of the present study was to investigate whether pentraxin 3 (PTX3) can be a new noninvasive marker for prediction of liver fibrosis in patients with NAFLD. We also aimed to evaluate the relationship between PTX3 and atherosclerosis in patients with NAFLD. Method. Fifty-four male patients with biopsy-proven NAFLD and 20 apparently healthy male volunteers were included. PTX3 levels were determined, using an ELISA method (R&D Sysytems, Quantikine ELISA, USA). To detect the presence of subclinical atherosclerosis in NAFLD, measurements of CIMT, FMD, and cf-PWV levels were performed. Results. PTX3 levels in NAFLD patients with fibrosis were higher than both NAFLD patients without fibrosis and controls (P=0.032 and P=0.028, respectively), but there was no difference between controls and NAFLD patients without fibrosis in terms of PTX3 levels (P=0.903). PTX3 levels were strongly correlated with cf-PWV (r=0.359, P=0.003), whereas no significant correlation was found with other atherosclerosis markers, CIMT and FMD. Conclusion. Elevated plasma PTX3 levels are associated with the presence of fibrosis in patients with NAFLD, independently of metabolic syndrome components. This study demonstrated that for the first time there is a close association between elevated PTX3 levels and increased arterial stiffness in patients with NAFLD.